Pengaruh Sektor Pariwisata Terhadap Pendapatan Asli Daerah (PAD) Provinsi di Pulau Jawa pada Tahun 2018-2022 - Arzeta Salsabila Yusuf Arzeta; Hendry Cahyono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Regional Original Revenue (PAD) plays a crucial role in the development and financial independence of a region. The tourism sector is considered to make a significant contribution to PAD and regional economic development. The purpose of this study is to determine how the tourism sector affects the Provincial Original Revenue (PAD) in Java Island in 2018-2022, using four independent variables, namely the number of hotels, the number of rooms, the number of tourist attraction objects, and the number of tourists. They research method used is multiple linear regression analysis and uses the Stata 17 analysis tool. The results in this study show that the number of hotels has a significant negative effect on local revenue (pad), the number of rooms hotels and the number of tourist attractions has a significant positive effect on local revenue (PAD), while the number of tourists has a non-significant positive effect on local revenue (PAD).